PENGAMBILAN KEPUTUSAN DALAM ORGANISASI PENDIDIKAN - Khabib Sharifudin (CV. ADIBA AISHA AMIRA, 2026)
Decision making is a cognitive process carried out by humans that causes them to choose a particular action or belief from a variety of available options, either rationally or irrationally. Decision making is essential for leadership, motivation, communication, coordination, and organizational change. Organizations can only operate if their leaders have the ability to make decisions and organize organizational members according to their positions and responsibilities. This study found that the following basic principles should be the basis for decision making in an educational organization: authority, credibility, reference, ethics, orientation, and scope. Based on these principles, various paradigms—classical, administrative, incremental, administrative-incremental, and contingency—are used to make decisions.